2021
DOI: 10.3390/ijerph18147603
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Government Subsidies on the Low-Carbon Supply Chain Based on Carbon Emission Reduction Level

Abstract: To improve low-carbon technology, the government has shifted its strategy from subsidizing low-carbon products (LCP) to low-carbon technology. To analyze the impact of government subsidies based on carbon emission reduction levels on different entities in the low-carbon supply chain (LCSC), game theory is used to model the provision of government subsidies to low-carbon enterprises and retailers. The main findings of the paper are that a government subsidy strategy based on carbon emission reduction levels can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…First, leaders should be aware of the importance of reducing carbon emissions for the development of the industry and set the reduction of carbon emissions as one of the main development goals of the enterprise, so as to lead the low-carbon development of the industry. Second, leaders should clarify the carbon emission requirements of policies and regulations on the industry, and strive to learn and apply low-carbon technologies in enterprise development to reduce carbon emissions and meet the requirements [ 80 ]. Third, leaders should actively participate in industry conferences and accumulate experience in reducing carbon emissions, so as to contribute to the low-carbon development of the industry.…”
Section: Discussionmentioning
confidence: 99%
“…First, leaders should be aware of the importance of reducing carbon emissions for the development of the industry and set the reduction of carbon emissions as one of the main development goals of the enterprise, so as to lead the low-carbon development of the industry. Second, leaders should clarify the carbon emission requirements of policies and regulations on the industry, and strive to learn and apply low-carbon technologies in enterprise development to reduce carbon emissions and meet the requirements [ 80 ]. Third, leaders should actively participate in industry conferences and accumulate experience in reducing carbon emissions, so as to contribute to the low-carbon development of the industry.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, there are also some researchers who have studied the interaction of operations, finance, and environment in an LCSC (e.g., [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]). Considering the emission-dependent random demand, Cao and Yu [ 34 ] studied the trade credit financing (TCF) and coordination problem in an LCSC under a cap-and-trade mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tang and Yang [ 36 ] examined the impacts of BCF and the power structure and found that early payment is a financing equilibrium. Moreover, the government can also provide subsidies and green credit for carbon emission reduction (e.g., [ 37 , 38 , 39 , 40 , 41 , 42 ]). Li et al [ 41 ] analyzed the impacts of government subsidies based on carbon emission reduction levels.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the pm 2.5 pollution has become a challenge in the process of industrial development all over the world, and the Yangtze River Delta of China is facing double pressure of economic development and environmental protection (Ji et al, 2021). The government has shifted from low-carbon products to low-carbon technologies in order to improve the level of low-carbon economy (Li et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%